Comrades at War: Soviet Radio Broadcasting during the 1979 Sino-Vietnamese War. Issue 4 (2nd October 2019) - Busch, Peter
Abstract : The Sino-Vietnamese War could have escalated into a wider confrontation involving the Soviet Union. Public communications played an important role in keeping the conflict limited. By focusing on transcripts of Soviet domestic radio produced by the British Broadcasting Corporation's Monitoring Service (BBCM), this article makes a contribution to our understanding of state-controlled broadcasting during the crisis. It also adds to our knowledge of Soviet radio in the late Cold War, arguing that it was comprehensive, varied and timely in communicating news about the war and that Soviet radio had achieved considerable sophistication in framing its message by the end of the 1970s. The article also discusses how the vast collection of BBCM radio transcripts, which consists of 'raw' transcripts that were not necessarily fed into the British and US government departments, allows us to assess the role broadcasting played in Soviet political messaging.